2007
DOI: 10.1002/polb.21098
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of poly(ethylene terephthalate) structures and conformations to alter properties

Abstract: The solid-state morphologies, structures, and chain conformations of poly (ethylene terephthalate) (PET) have been reorganized/altered from those normally produced by solution and melt processing. This has been achieved by two distinct methods: (1) formation of a crystalline inclusion compound (IC) between guest PET and host c-cylodextrin (c-CD), followed by removal of the host c-CD and coalescence of the guest PET (c-PET) and (2) rapid precipitation of PET from a warm trifluoracetic acid solution into a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 87 publications
4
49
0
Order By: Relevance
“…Though not presented here, the FTIR spectra of asr‐ and p‐PETs are similar except for greater resolution in the p‐PET spectrum 4. Improved resolution was also seen for c‐PET3 and attributed to its high crystallinity and non‐crystalline regions consisting of chains pre‐dominantly in the gauche ± trans gauche ${\mp} $ conformations (see Figure 3), which guest PET chains in the channels of its precursor γ‐CD‐IC crystals are believed to adopt 3–5, 7. PET cast from TFA/chloroform solution exhibited an FTIR spectrum closely similar to that of asr‐PET 3…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Though not presented here, the FTIR spectra of asr‐ and p‐PETs are similar except for greater resolution in the p‐PET spectrum 4. Improved resolution was also seen for c‐PET3 and attributed to its high crystallinity and non‐crystalline regions consisting of chains pre‐dominantly in the gauche ± trans gauche ${\mp} $ conformations (see Figure 3), which guest PET chains in the channels of its precursor γ‐CD‐IC crystals are believed to adopt 3–5, 7. PET cast from TFA/chloroform solution exhibited an FTIR spectrum closely similar to that of asr‐PET 3…”
Section: Resultsmentioning
confidence: 92%
“…During the course of forming the PET‐γ‐CD‐IC,3 several control experiments were conducted. It was observed that PET rapidly precipitated (p‐PET) from a trifluoroacetic acid (TFA)/chloroform solution upon slow addition to rapidly stirred acetone (see Supporting Information) evidenced behavior closely similar to that of c‐PET 4, 5…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…PET was structurally modified by a precipitation technique [15,16]. Briefly, 6% by (w/v) of PET was dissolved in TFA and heated to 50 • C with rapid stirring to completely dissolve the polymer.…”
Section: Preparation Of R-pet and R-pet With Mwcntmentioning
confidence: 99%